PROSPECTS OF USING THE ZINAMA-ZINA METHOD IN TEACHING REAL PARTICLE PHYSICS (Journal of Science-Innovative Research in Uzbekistan, 2024)
This article focuses on the application of the modern method used in the teaching of real elementary particle physics in the classroom, its demonstration and movement, and the fact that it is interesting and understandable for students.And information about each group of elementary particles is presented.